MEMAHAMI KEBIJAKAN PENGEMBANGAN AGROWISATA DI KABUPATEN CIAMIS: DINAMIKA SUMBER DAYA ALAM LOKAL DAN KEBUDAYAAN - Nurwanda, Asep; Badriah, Elis; Nursetiawan, Irfan (Fakultas Politik Pemerintahan, 2020)
This study aims to determine the condition of agro-tourism based on local natural resources and local wisdom based on the culture of Ciamis district. The effort to develop agro-tourism based on local culture is a form of effort to improve the quality and quantity of infrastructure and improve the quality of resources as an effort to develop tourism. with the existence of this agro-tourism concept, it is not only a business or business in the service sector that markets services towards consumer fulfillment of cool air, and beautiful scenery and environment, but is also able to take a role as a place for promotion of agricultural products, as a place of education for residents , gives hope to the potential to develop products from agribusiness and can become a new growth area. Therefore, agro-tourism is able to become a source of regional economy. Research methods use a qualitative descriptive approach, so that the application of activities in developing agro-tourism based on local natural resources and based on cultural wisdom, there is still a lack of assistance in human resource development and training and lack of communication between the government and community groups. culture and business groups.